2020
DOI: 10.1007/s00134-020-06073-8
|View full text |Cite
|
Sign up to set email alerts
|

Epileptic seizure discharges in patients after open chamber cardiac surgery—a prospective prevalence pilot study using continuous electroencephalography

Abstract: Purpose: Patients undergoing cardiac surgery often develop delirium which increases the risk of postoperative morbidity and leads to a reduced quality of life. Retrospective studies show a higher incidence of delirium in patients with seizures. However, these studies do not systematically detect subclinical seizures, so the incidence of seizures after cardiac surgery remains speculative. The objective of this study is to determine the prevalence of electrographic seizures after elective open-chamber cardiac su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…A significant increase in length of intensive care unit (ICU) stay was observed in the group of EEG seizures after CPB as compared with the no EEG seizures group both in adults (WMD = 5.2 days; 95% CI: 1.908–8.475; P = 0.002) ( 17 , 23 , 24 ) and pediatrics (WMD = 7.1 days; 95% CI: 3.239–10.965; p < 0.001) ( 20 , 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…A significant increase in length of intensive care unit (ICU) stay was observed in the group of EEG seizures after CPB as compared with the no EEG seizures group both in adults (WMD = 5.2 days; 95% CI: 1.908–8.475; P = 0.002) ( 17 , 23 , 24 ) and pediatrics (WMD = 7.1 days; 95% CI: 3.239–10.965; p < 0.001) ( 20 , 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, 26% of patients demonstrated epileptiform discharges during cardiac surgery. In another study on postoperative patients in the cardiac surgical care unit, Tschernatsch et al ( 27 ) found the incidence of epileptiform discharges and abnormal EEGs to be 9% and 33%, respectively. The high incidence of epileptiform discharges in our study may be attributed to the fact that we analyzed intraoperative EEG data and abnormal electrical activity in the brain caused by anesthesia drugs and changes in cerebral blood flow during CPB.…”
Section: Discussionmentioning
confidence: 98%
“…Of note, we specifically recorded the incidence of clinically overt stroke and epilepsy, and distinguished between stroke and global cerebral ischemia. In contrast, other studies often only focused on stroke or epilepsy 6,8,9,17,[19][20][21] .…”
Section: Discussionmentioning
confidence: 99%